Drug-related problems identified in post-discharge medication reviews for patients taking warfarin - Stafford, Leanne; Stafford, Andrew; Hughes, J.; Angley, M.; Bereznicki, L.; Peterson, G. (Springer Science + Business Media, 2011)
Objective: To characterise the nature of the drug-related problems with warfarin therapy identified in pharmacist-conducted medication reviews during a collaborative post-discharge warfarin management service, with a focus on potentially serious drug interactions. Setting: Australian community pharmacy practice. Method Medication review reports submitted by pharmacists to patients’ general practitioners as part of the service were reviewed and the type and clinical significance of the warfarin-associated drug-related problems, and the pharmacists’ recommendations were classified. The prevalence of prescribing of ‘potentially hazardous’ warfarin drug interactions was investigated and compared with the frequency of documentation of these interactions in the medication review reports. Main outcome measure: The number and nature of warfarin-associated drug-related problems identified and the rate of documentation of ‘potentially hazardous’ warfarin drug interactions in the reports from pharmacist-conducted medication reviews. Results A total of 157 warfarin-associated drug-related problems were documented in 109 medication review reports (mean 1.4 per patient, 95% CI 1.3–1.6, range 0–5). Drug selection and Education or information: were the most commonly identified warfarin-associated drug-related problems; most drug-related problems were of moderate clinical significance. Eight of 23 potentially serious warfarin drug interactions (34.8%) were identified in the medication review reports. Conclusion: Pharmacists addressing drug selection and warfarin education drug-related problems during medication reviews may have contributed to the positive outcomes of the post-discharge service. Warfarin drug interactions were frequently identified; however, well-recognised potentially hazardous interactions were under-reported. Improved communication along the continuum of care would permit improved targeting of drug-related problem reporting, especially in relation to preventable drug interactions.